(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2023)
The article analyses the crucial points of Don Lorenzo Milani’s message, included in “Letter to a teacher” – the analysis of the Italian school and the three proposals for change, starting from his experience of the Barbiana school – as well as the distortions and improper use, after his death, of the message regarding teaching programs, school selection and personalization of paths. Finally, the article argues that Don Lorenzo Milani walked his short path as an ardent “pilgrim of the Absolute”.